Student Teams Achievement Division with a Learning Video to Increase Students` Achievements and Learning Motivation in Social Science Learning - Ais Murjianti; Hermanu Joebagio; Nunuk Suryani (Yupa: Historical Studies Journal, 2018)
This research aims to measure the effectiveness of the implementation of learning model STAD using video to improve the students’ motivation and students ‘achievement. The type of this research is classroom action research, that is conducted at Sidoharjo Junior High School 2 Sragen, Indonesia. The implementation of cooperative learning with STAD model using video could improve the students` learning achievement. The average score was 76, 13, and the percentage of minimal classical completeness reach 87, 09 %. However, perceived on the classical completeness criteria, all of the students have completed the criteria, and reach 85 % of the learning target. The implementation of STAD using natural resources video could improve the student`s motivation. The result of the research shows the average score of 83, 97%, and the percentage of minimum criteria shows 80%.